HUBUNGAN TINGKAT PENGETAHUAN SISWA TENTANG DAMPAK ROKOK BAGI KESEHATAN DENGAN PERILAKU MEROKOK SISWA DI SMA PGRI BOLO TAHUN 2015 - Nurwahidah Nurwahidah; Awan Dramawan; Abdul Haris (Jurnal Kesehatan Prima, 2015)
Abstract: Smoking is an substance additive threaten because inside contain subtance danger body . world healty organization (WHO) and some articles scientific explain in every smoke contain ± 4000 scientific poison and between 43 character carsinogenik ( stimulate grown of cancer ), behave that , eventually more controversial about smoke circle on student. Be based on the top , reseacher take title “ relationship level knowlage student impact about healty and attitude smoking student in High School PGRI Bolo “. purpose for identification level relationship student knowlage about impact of smoking about healty and attitude smoking student in High School PGRI Bolo and using design reseacher descriptif analitik approacment method cross sectional , with 40 totaling sample respondent in accordance with the inclusion criteria ware taken by total sampleing technique . the experiment was conducted for 4 days on 6–9 march 2015 using a questionnaire. Based on the result of statistical test of pearson correlations with the aid of computer equipment (SPSS system), where the value of the proposed α < 0,05 significance of test result obtained value r = 0,887 significant value p= 0,0000, that is to say α < 0,05 (0,0000 < 0,05) , it means there is a strong relationship between the level of studance knowlage about the impact of smoking on healt and smoking bahavior of student in High School PGRI Bolo. Conclusion that respinden knowlageable anough about  smoking behavior in the medium category, this means the better the student level of knowlage about the effect of smoking on health , the more negative behavior of student smoking in High School PGRI Bolo.